Linking multisectoral economic models and consumption surveys for the European Union. Issue 1 (2nd January 2022) - Cazcarro, Ignacio; Amores, Antonio F.; Arto, Inaki; Kratena, Kurt
Abstract : Multisectoral models usually have a single representative household. However, more diversity of household types is needed to analyse the effects of multiple phenomena (i.e. ageing, gender inequality, distributional income impact, etc.). Household consumption surveys' microdata is a rich data source for these types of analysis. However, feeding multisectoral models with this type of information is not simple and recent studies show how even slightly inaccurate procedures might result in significantly biased results. This paper presents the full procedure for feeding household consumption microdata into macroeconomic models and for the first time provides in a systematic way an estimation of the bridge matrices needed to link European Union Household Budget Surveys' microdata with the most popular multi-regional input–output frameworks (e.g. Eurostat, WIOD, EORA, OECD).